Urban Planning and Mobility: Evaluation of a Road Infrastructure Proposal in Juazeiro do Norte - Santos, João Evangelista Dantas dos (Brazilian Journal of Production Engineering, 2024)
The study focused on the analysis of the replacement of certain road infrastructures in Juazeiro do Norte, Ceará, as proposed by the PDM, aiming to improve flow and road safety. The research aimed to validate the proposal of the public power to replace a semaphore plan with a roundabout, with simulations made in Aimsun software. The method used combined quantitative and qualitative analyzes to evaluate the effects of this change in addition to collected data on CO2 emission, average speed and travel time. Qualitative analysis included detailed observations of traffic behavior under different implementation scenarios, while quantitative results showed that the replacement of traffic lights with roundabouts can improve traffic flow and reduce congestion, and increase road safety. However, implementing certain measures without proper planning may not achieve the expected benefits, requiring continuous adaptations during tests. It was concluded that an integrated and sustainable urban planning, based on empirical data and detailed technical data, which should force continuous investments in road infrastructure and modernization of facilities for the supply of public transportation and other measures that are essential to promote mobility, which are crucial that should force continuous investments that are essential to promote mobility. Efficient, safe and sustainable urban.
Keywords: Traffic Simulation; Public Management; Time of travel; Average speed; Urban planning